PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT YANG DIBANTU DENGAN MEDIA TTS PADA PEMBELAJARAN BIOLOGI SISWA KELAS X MAN GUNUNG PADANG PANJANG - Febriyanto, Febriyanto; Zulmardi, Zulmardi; Delfita, Rina (Jurnal Pembelajaran MIPA, 2014)
The porpuse of this research is to know the student result study in Biology subject, by giving cooperative type Game tournament assisted crossword. Kind of this research is pseudo experiment, research design is randomized control posttest only designs group. Research instruments are learning result test. Data was analysed by T test. The result show that differences of avarge value, standard deviation and variances of experiment and control classes. Hypothesis was accepted,Â therefore the condusion of this research are students learning result at experiment class with cooperative type Â Game tournament assisted crossword better than control class.Key words : Kooperatif is NHT Â TGT, Croswoord, Biology